Digital Game-based Learning: Exploring the Use of Mobile Legends in Arabic Language Skills - Husna, Ilya; Maiza, Zikrawahyuni; Febriani, Suci Ramadhanti; Dinata, Rahmat Satria; Amri, Fauzul Fil (AL-TA'RIB : Jurnal Ilmiah Program Studi Pendidikan Bahasa Arab IAIN Palangka Raya, 2024)
Among the negative impacts of Mobile Legends are dependence, loss of productivity, and health degradation. This research explored the other side of Mobile Legends, focusing on their positive impacts on learning. This study aims to explore the benefits of Mobile Legends digital games in Arabic language skills and analyze the use of Arabic in Mobile Legends games. The approach in this study is qualitative descriptive. The research sample was Arabic Language Education students of UIN Imam Bonjol Padang. The results showed: 1) the game used Arabic and players could improve listening to the Arabic vocabulary used in the game; 2) this game used Arabic in communication interactions between teams and opponents so that communication between players using Arabic-supported speaking skills; 3) this game helped users understand words and phrases used in the context of specific situations and team interactions; 4) besides the language aspect, the cultural aspect also influenced this game, Khaleed's character is identified as Khaleed bin Walid the valiant hero of Islam from Arabia. This research outlines that the Mobile Legends application can improve students' Arabic skills, especially listening, speaking, and reading.